Comparative voltammetric and FTIRRAS study on the electro-oxidation of thiourea and methyl-thioureas on platinum in aqueous acid solutions - Bolzán, Agustín Eduardo (2004)
A comparative voltammetric and spectroscopic study on thiourea, methylthiourea, 1,3 dimethylthiourea and tetramethylthiourea electro-oxidation is presented. The investigation was performed at platinum electrodes in aqueous acid solutions in the potential range between 0.05 and 1.6 V (versus SHE). The electro-oxidation of thioureas starts at ca. 0.55 V and it involves at least two reaction stages irrespective of their nature. The first electro-oxidation stage occurs in the range 0.55–0.9 V and involves the formation of a soluble disulphide derivative influenced by the blockage of the electrode surface. The second electro-oxidation stage occurs in the range 0.9–1.6 V and it involves a complex electrochemical process yielding products such as carbon dioxide, sulphate ions, CN- and CO-containing species. The second electro-oxidation stage is likely mediated by the oxygen-containing layer that is produced electrochemically on platinum in that range of potential. The gradual depletion of thioureas and the progressive formation of soluble products in the thin solution layer in contact with the electrode are followed through changes in the band intensities of IR spectra. From the correlation between voltammetric and spectroscopic data a description of global reactions involving the electro-oxidation of thioureas to soluble products in both potential ranges is presented. The proposed reaction pathways are consistent with the participation of different adsorbates as was reported earlier for thioureas on platinum.